Displaying and performing: Polish transnational families in Ireland Skyping grandparents in Poland. (August 2018) - Share, Michelle; Williams, Cayla; Kerrins, Liz
For transnational families, doing and displaying family is enabled by communications technologies like Skype. We draw on the concept of family display in an analysis of data from a qualitative study of Polish migrant parents resident in Ireland on their Skype use. Skype functions as an important tool for family display, in the perinatal period, and for displays of intergenerational solidarity. The communicative underpinnings of a video-Skype call are such that a significant element of performance is required in which parents, children and grandparents engage as performers, directors and audiences to create meaningful communication. Such communication is effortful, involves emotion work and belies assumptions about the ease of transnational family practice through Skype.